2014
DOI: 10.1159/000356549
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Inflammatory Pathway as a Therapeutic Tool for Major Depression

Abstract: In the last decades convergent findings from several lines of evidence has revealed a robust association between major depressive disorder (MDD) and inflammatory pathways. Despite this, the translation of these findings into new and better treatments for MDD has not occurred. The objective of this study is to comprehensively review what is already known with reasonable certainty on inflammatory pathways in MDD, to clarify some points that have been insufficiently studied and to discuss the implications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 92 publications
3
17
0
Order By: Relevance
“…Alterations in serum levels of cytokines have been demonstrated in several psychiatric disorders in adults (11,12,14,30). In pediatric population, TBARS, thiobarbituric acid reactive substances; BDNF, brain-derived neurotrophic factor; IL-2, interleukin-2; IL-4, interleukin-4; IL-6, interleukin-6; IL-10, interleukin-10; IL-17A, interleukin-17A; IFN-c, interferon-gamma; TNF-a, tumor necrosis factor-a; CCL11, chemokine (C-C Motif) ligand 11; IP-10, IFN-c inducible protein 10; MCP-1, monocyte chemoatractant protein 1; sTNFR1, soluble TNF-a receptor 1; sTNFR2, soluble TNF-a receptor 2. the data available are less substantial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in serum levels of cytokines have been demonstrated in several psychiatric disorders in adults (11,12,14,30). In pediatric population, TBARS, thiobarbituric acid reactive substances; BDNF, brain-derived neurotrophic factor; IL-2, interleukin-2; IL-4, interleukin-4; IL-6, interleukin-6; IL-10, interleukin-10; IL-17A, interleukin-17A; IFN-c, interferon-gamma; TNF-a, tumor necrosis factor-a; CCL11, chemokine (C-C Motif) ligand 11; IP-10, IFN-c inducible protein 10; MCP-1, monocyte chemoatractant protein 1; sTNFR1, soluble TNF-a receptor 1; sTNFR2, soluble TNF-a receptor 2. the data available are less substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic proteins, immune-inflammatory axis, and oxidative stress pathways have been reported to impact brain structure and function in a time and context-dependent manner and are relevant to neurodevelopment in physiological conditions (8,9). Several studies have reported abnormalities in neurotrophic factors, such as the brain-derived neurotrophic factor (BDNF), inflammatory mediators such as cytokines and in oxidative stress balance with increases in oxidative markers such as thiobarbituric acid-reactive substances (TBARS) in adult psychiatric disorders, including mood disorders, addictions, and schizophrenia (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In depression, proinflammatory cytokines were found to interact with the HPA axis, to stimulate the serotonin-depleting indolamine-2,3-dioxygenase and to trigger serotonin reuptake [6,8,9]. Levels of proinflammatory cytokines were repeatedly found to be elevated in depressed patients as well as in animal models of depression [6,10,11], potentially representing an inflammation-associated specific subtype of MDD [12,13,14] and a target for new antidepressant treatment strategies [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Changes in proinflammatory and cell‐mediated immune cytokines have been thoroughly documented in psychiatric diseases such as major depressive disorder (MDD). In fact, in addition to genetic and environmental factors, a robust association has been defined for MDD, immune response, and inflammation . Evidence suggests that antidepressants, such as the tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRIs), may function to normalize cytokine levels, and this may be an additional therapeutic mechanism secondary to their effect on neurotransmitters .…”
Section: Microbiome Inflammation and Moodmentioning
confidence: 99%